2016
DOI: 10.1080/07448481.2016.1207645
|View full text |Cite
|
Sign up to set email alerts
|

Social connectedness and life satisfaction: Comparing mean levels for 2 undergraduate samples and testing for improvement based on brief counseling

Abstract: Social connectedness is an important antecedent of life satisfaction for undergraduates. Brief counseling can increase transition students' social connectedness and life satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
8
0
3
Order By: Relevance
“…The dimension connectedness refers to communication in various dimensions such as communication with family, friends, self, work, and the place of residence. Blau et al in the study on undergraduate students concluded that social communication promotes life satisfaction, and that as communication expands, the level of satisfaction increases (32). The results of another study showed that communication with friends leads to more life satisfaction, higher self-confidence, and happier life (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…The dimension connectedness refers to communication in various dimensions such as communication with family, friends, self, work, and the place of residence. Blau et al in the study on undergraduate students concluded that social communication promotes life satisfaction, and that as communication expands, the level of satisfaction increases (32). The results of another study showed that communication with friends leads to more life satisfaction, higher self-confidence, and happier life (33,34).…”
Section: Discussionmentioning
confidence: 98%
“…Mahon et al (2015) found a significant decrease in counselor-reported client symptom severity. Blau et al (2016) found that the means of social connectedness and life satisfaction significantly increased over time for 28 non-urgent undergraduates, with a median of four counseling sessions (after initial triage assessment).…”
Section: Generally Brief Nature Of College Counselingmentioning
confidence: 95%
“…Mahon et al (2015) found a significant decrease in counselor-reported client symptom severity. Blau et al (2016) found that the means of social connectedness and life satisfaction significantly increased over time for 28 undergraduates, with a median of four counseling sessions (after initial triage assessment). The current study measured a different set of antecedent variables, i.e., mental distress, mental health concerns, and self-esteem, as well as life satisfaction, and collected a longer-term sample of students in counseling (up to a median of 10 weeks, range of eight to 12 weeks), while testing two hypotheses.…”
Section: Brief Nature Of College Counselingmentioning
confidence: 96%